STRATEGI GRUP GAGAK RIMANG DALAM MELESTARIAN SENI KUDA LUMPING DI TEMANGGUNG - Hamidulloh Ibda; Intan Nasution (Jantra., 2019)
Kuda Lumping is a Javanese traditional dance commonly called Jaran Kepang, Jathilan, Jaran Eblek, and others. Accompanied by gamelan music, the dance involves a group of dancers who “ride” on colourful flat horses made of bamboo. The data of this descriptive qualitative research were drawn from interviews and observation. The aim of this research describes how the Gagak Rimang group was established, its form of performance, and its strategies to preserve Kuda Lumping dance. The problems faced by the Gagak Rimang group are among others finance, rehearsals, personnel, lack of female dancers. However, there are circumstances which profit the group, such as, competition among groups of Kuda Lumping, support from the local government, the synergy that has developed between the group and mass organizations, societies, as well as free promotion on social media by its spectators.